2014
DOI: 10.1021/pr500849x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction between Heterodimeric αvβ6 Integrin and Urokinase Plasminogen Activator Receptor (uPAR) Using Functional Proteomics

Abstract: Urokinase plasminogen activator receptor (uPAR) and the epithelial integrin αvβ6 are thought to individually play critical roles in cancer metastasis. These observations have been highlighted by the recent discovery (by proteomics) of an interaction between these two molecules, which are also both implicated in the epithelial-mesenchymal transition (EMT) that facilitates escape of cells from tissue barriers and is a common signature of cancer metastases. In this study, orthogonal in cellulo and in vitro functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…The αvβ6•uPAR interaction originally proposed by Saldanha et al and Sowmya et al has now been confirmed by Ahn et al using two orthogonal techniques: proximity ligation assays (PLA) and overlapping peptide array blots [81]. PLA is an emerging method that allows direct detection of protein•protein interactions in cellulo due to the close proximity of interacting proteins (30-40 nm) (refer to Weibrecht et al for a comprehensive review [91]).…”
Section: αVβ6 Interacts With Domain III Of Upar Through the αV Subunitmentioning
confidence: 95%
See 4 more Smart Citations
“…The αvβ6•uPAR interaction originally proposed by Saldanha et al and Sowmya et al has now been confirmed by Ahn et al using two orthogonal techniques: proximity ligation assays (PLA) and overlapping peptide array blots [81]. PLA is an emerging method that allows direct detection of protein•protein interactions in cellulo due to the close proximity of interacting proteins (30-40 nm) (refer to Weibrecht et al for a comprehensive review [91]).…”
Section: αVβ6 Interacts With Domain III Of Upar Through the αV Subunitmentioning
confidence: 95%
“…Active plasmin is generated from plasminogen by uPA upon binding its cognate receptor, uPAR [80]. Under these conditions, uPA is relatively Bshielded^from the specific serpin inhibitors (PAI-1, PAI-2 and protease nexin), as are other proteases on the cell surface in the periplasmic space [81]. Once active, plasmin is capable of driving extensive ECM component degradation (e.g.…”
Section: β6 Expression Promotes Erk2 Activationmentioning
confidence: 99%
See 3 more Smart Citations